Myasthenia gravis - Demir, Caner Feyzi; Taşci, Irem (Akademisyen Yayinevi Kitabevi, 2021)
Myasthenia gravis (MG) is an autoimmune disease that impairs neuromuscular transmission and causes muscle weakness that worsens with fatigue. The first description of MG was made by an English doctor named Thomas Willis in 1672 in his book \"De anima brutorum\". The term \"myasthenia gravis\" was first used by Friedrich Jolly in 1895, with \"myasthenia\" meaning muscle weakness in Greek and \"gravis\" meaning severe in Latin.The incidence and prevalence of MG have been calculated based on 55 studies published between 1950 and 2007, and it has been found to affect 5.3 and 77.7 million people worldwide, respectively. Furthermore, it has been revealed that the prevalence of MG has been increasing over the past half-century. The reasons for this increase may be attributed to factors such as increased knowledge about the disease and higher diagnostic rates, increased treatment options, advancements in intensive care technology, and improved survival rates among patients. While MG typically affects young individuals, recent epidemiological studies have shown an increased incidence of MG in individuals over the age of 50. MG has a bimodal incidence pattern with two peaks in women, occurring at ages 20-30 and over 50, whereas in men, it is typically seen in individuals over the age of 50. Clearly, MG is more common in young females and does not show a gender preference in older ages. However, the development of MG in children under the age of 1 is unlikely.The pathogenesis of MG involves an autoimmune attack against the postsynaptic acetylcholine receptor (AChR) at the neuromuscular junction. AChR antibodies disrupt neuromuscular transmission in patients with generalized MG (GMG) and ocular MG (OMG). In AChR-negative MG, muscle-specific receptor tyrosine kinase (MuSK) has been identified as another antigenic target. Recently, another autoantibody targeting low-density lipoprotein receptor-related protein 4 (LRP4) has been detected in AChR-negative and MuSK-negative MG. AChR antibodies can be detected in approximately 85% of GMG patients and 50% of OMG patients. MuSK antibodies can be found in 70% of patients without AChR antibodies and these antibodies belong to the IgG4 isotype. LRP4 antibodies have been found to be positive in 18.7% of seronegative MG patients in a recent study evaluating a large patient series. LRP4 antibodies contain complement-activating IgG1 isotype that inhibits agrin-induced AChR clustering. Agrin antibodies are rarely detected in seronegative MG patients and sometimes in GMG patients. © 2021 Akademisyen Kitabevi A.Ş. All rights reserved.